Umbilical cord care practices and associated factors among mothers who gave birth in the last six months in hetosa district, Arsi zone, Ethiopia 2021: Community-based mixed design - Genat Balcha Abdi; Bekalu Kassie Alemu; Tensae KassaYizengaw; Beker Ahmed Hussein (Heliyon)
Background: Cord care is the series of steps applied to handle the umbilical cord after delivery of the newborn. Despite increasing the number of primary health facilities, unhygienic cord care remains persist. Objective: To assess umbilical cord care practices and associated factors among mothers who gave birth in the last six months in Hetosa district, Arsi zone, Ethiopia, 2021. Methods: A mixed-type cross-sectional study design was conducted in the Hetosa district of Arsi zone, from April 15 to May 15, 2021, with 550 mothers using a systematic random sampling technique for quantitative study. Quantitative Data were collected using a structured pretested questionnaire, entered into EpiData version 3.1, and then exported to SPSS version 25 for analysis. Factors associated with outcome variables were identified using logistic regression analysis. Qualitative data was collected through twelve in-depth interviews and analyzed thematically. Result: Overall good cord care practice was 53.4 % [95%CI, 49, 58]. Being in age group ≤ 24years (AOR = 4.55, 95 % CI; 2.08, 9.98) and 24–32years (AOR = 3.70, 95 % CI; 1.98, 6.94), among those who attend primary school (AOR = 5.26, 95 % CI: 2.50, 11.04) and secondary and above (AOR = 3.63, 95 % CI: 1.61, 8.18), health facility delivery (AOR = 5.09, 95 % CI; 2.95, 8.78), and having good knowledge about cord care(AOR = 8.58, 95 % CI; 5.09, 14.46) were statically significantly associated with good umbilical cord care practice. Participants believed that applying fresh butter around the stump could protect the baby. Conclusion: and recommendation: The study found that the percentage of mothers practicing good cord care was low. To improve this, policies and strategies should focus on women's education, encouraging institutional delivery and family planning use among aged mothers, and health education during ANC visits and addressing community beliefs through culturally sensitive health promotion strategies particularly focusing on older mothers and traditional birth attendants to improve cord care practices.